Outward foreign direct investment from economies in transition in a global context - Kálmán Kalotay (Journal for East European Management Studies, 2003)
They are barely visible on the global scene. But it is in part so because official statistics have difficulties in reflecting their real size. They are nevertheless gaining in importance, representing a challenge for those who want to understand why and how they expand. Analysts are at the beginning of their quest for explaining how transnational corporations from economies in transition fit into a new zoology of international business, in which there is space for many more species than previously believed. Policy makers in economies in transition, too, are trying to grasp with the dilemma that outward FDI presents for them: on the one hand, it strengthens the international competitiveness of the firms; on the other, it is an outflow of resources. On balance, some of the countries in transition, e.g. Hungary and Slovenia, have decided to promote outward FDI. – – Auf globaler Ebene sind sie kaum zu sehen. Zum Teil liegt es daran, dass es schwierig ist, sie in offiziellen Statistiken zu erfassen. Dennoch werden sie immer wichtiger und stellen eine Herausforderung für jene dar, die danach fragen, wie und weshalb sie expandieren. Analysten stehen erst am Anfang der Aufgabe, transnationale Gesellschaften aus Übergangsländern hinreichend zu definieren und einzuordnen. Politiker in Übergangsökonomien versuchen ebenfalls das Dilemma, das ausländische Direktinvestitionen (FDI) mit sich bringen, zu begreifen: Auf der einen Seite stärken sie die internationale Wettbewerbsfähigkeit der Firmen, auf der anderen Seite stellen sie einen Abgang von Ressourcen dar. Nichtsdestotrotz haben sich einige Übergangsländer wie Ungarn und Slowenien dazu entschlossen, FDI zu fördern.
Keywords: 650; Outward foreign direct investment; international business; transnational corporations